ANALISIS EFEKTIVITAS DANA BANTUAN OPERASIONAL PENYELENGGARAAN (BOP) PENDIDIKAN KESETARAAN DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SELUMA - Sutardi, Dodo; Sisman, Sisman; Aprianty, Henny; Noviyanto, Hernowo (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
This research aims to assess the effectiveness of the management of special allocation funds (DAK) non-physical aid provisions (BOP) equality in the pusa of public study activities (PKBM) and the SPNF SKB in the Dinas Education and culture of Seluma district. The research, it uses qualitative research, data-retrieval instates using observation data masking techniques, interview and documentation and then it will be analysed Raising in Khadafi and shopping (2017) is key The management oh the special allocation fund (BOP) non-physical cooperation arrangement (BOP), equality of a. Programmical Target, b. Socialization Program, c. Purpose Program, d. Monitoring Program Seluma chairman lembaga district, treasure and dapogial operator SPNF SKB, PKBM Darma Mulya, PKBM Gerak Mitra dan PKBM Ar-hasanah. Recearch result are already effective management of special allocation funds (DAK) non-physical operations assistance arrangements (BOP) equality in the community learning centre PKBM and SPNF SKB at Seluma Country education and culture services.